Engaging Millennial Students in Social Justice from Initial Class Meetings to Service Learning. (12th September 2013) - Cavallero, Jonathan J.
Abstract: This chapter argues that the affirmation of Millennial students' egos is an essential aspect of a social justice curriculum.